The Effect of Resilience and Workload on Organizational Commitment of Criminal Investigation Investigators Mediated by Job Stress - Hussein, Kresnawan; Soeling, Pantius Drahen (Advances in Social Sciences Research Journal, 2020)
Organizational commitment is needed by the Denpasar City Resort Police to achieve organizational goals and create a condusive economic, political, social, and cultural situation. The high workload puts the individual in a job stress situation that reducing the productivity and commitment of the investigators to the organization. However, the investigators who are resilient will be able to break down the stress into positive things to increase the productivity and feel as a part of the National Police organization. This research aims to analyze the effect of resilience and workload on organizational commitment of criminal investigation investigators mediated by job stress variable. The research method used was Explanatory Survey Method, while the analytical method used was (PLS-SEM) with software SmartPLS version 3.0. This research used the entire population involving 220 criminal investigation investigators of Denpasar City Resort Police. The results of the research explained that the resilience variable had a negative and insignificant effect on job stress variable but the positive and significant effect on organizational commitment variable. While workload variable had a positive and significant effect on job stress variable but it had the negative and significant on organizational commitment variable. Meanwhile, job stress variable had negative and significant on organizational commitment variable. Based on the results of this research, resilience can reduce job stress arising from the high workload that increasing organizational commitment of the criminal investigation investigators studied.